Appendicular fractures of traumatic etiology in dogs: 955 cases (2004-2013) - Libardoni,Renato do Nascimento (2016)
ABSTRACT: Orthopedic diseases are common in dogs and cats, especially, those caused by traumatic injury. Overall, among the significant changes in this group, the fractures are the major cause of pain and dysfunction in dogs of all ages, sizes and breeds. Therefore, a retrospective study of dogs examined between January 2004 and December 2013 at the University Veterinary Hospital of Universidade Federal de Santa Maria, was conducted aiming to identify and determine the prevalence of appendicular fractures caused by trauma and characterizing the population/etiology. In a population of 1,200 dogs with suspected traumatic orthopedic diseases in the locomotor system, 955 (79.6%) had appendicular fractures. Of the dogs 23.5% had fractures on the femur (n=225), 23.4% had pelvic fractures (n=223), 22% had tibial and fibular fractures (n=210), 17.6% had radius and ulna fractures (n=168), 7.5% had humeral fractures (n=72) and 6% had distal limb fractures (tarsus, carpus, metacarpus, metatarsus and phalanges (n=57)). The most frequent cause was car accidents (72.2%). Most affected dogs were male (52.5%), juvenile (42%), mixed breed (51.4%) and small size (42.7%). In conclusion, the profile of dogs with fractures in the Central Region of Rio Grande do Sul State is: male dogs, mixed breed, immature and small size, presenting femoral fractures by car accident.